(untitled) (Bangladesh Journal of Plant Taxonomy, 2024)
Three new records of angiosperms belonging to the genera Cinnamomum, Litsea, and Neolitsea of the family Lauraceae are described and illustrated from Bangladesh. Following critical examination, two voucher specimens of Lauraceae collected from Cox’s Bazar and Rangamati districts, and housed in DACB and BFRIH, respectively, were identified as Cinnamomum subavenium and Litsea glabrata. Two other specimens recently collected from the Lathitila forest of Moulvibazar during the floristic explorations conducted in the northeast region of Bangladesh were identified as Neolitsea foliosa. These three species are reported here as new to the flora of Bangladesh. A detailed taxonomic description, including data on ecology, distribution, and use, representative specimens examined, and an illustration of each of these species have been provided. Bangladesh J. Plant Taxon. 31(2): 301-309, 2024 (December)